Effect of Accounting Information Systems for Credit Sales and Trade Receivables on Cash Receipts - Silvi Nurizzati (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This research was conducted at PT Indokapur Jaya. The main purpose of this study is to determine the influence of accounting information system of credit sales and accounts receivable to cash receipts at PT Indokapur Jaya. The method used in this research is descriptive method and verification method by using quantitative approach. The data used in this study is the primary data. Data collection is done by direct observation, interviews, questionnaires and literature done by reading and studying books related to the problem. The population used for this research is 30 persons, they consist of finance department, sales department, delivery department, warehouse part, credit section, billing section and receivable part at PT Indokapur Jaya. The result of this research is the accounting information system of credit sales and accounts receivable jointly and significantly affect the cash receipt at PT Indokapur Jaya.